An energetic perspective on tissue regeneration: The costs of tail autotomy in growing geckos - Starostová, Zuzana; Gvoždík, Lumír; Kratochvíl, Lukáš (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2017)
Tail autotomy is a crucial antipredatory lizard response, which greatly increases individual survival, but at the same time also compromises locomotor performance, sacrifices energy stores and induces a higher burden due to the ensuing response of regenerating the lost body part. The potential costs of tail autotomy include shifts in energy allocation and metabolic rates, especially in juveniles, which invest their energy primarily in somatic growth. We compared the metabolic rates and followed the growth of juvenile males with and without regenerating tails in the Madagascar ground gecko (Paroedura picta), a nocturnal ground-dwelling lizard. Geckos with intact tails and those that were regrowing them grew in snout-vent-length at similar rates for 22weeks after autotomy. Tail regeneration had a negligible influence on body mass-corrected metabolic rate measured at regular intervals throughout the regenerative process. We conclude that fast-growing juveniles under the conditions of unrestricted food can largely compensate for costs of tail loss and regeneration in their somatic growth without a significant impact on the total individual body mass-corrected metabolic rate.
Keywords: Body Size; Weight Gain; bazální metabolismus; Lizards; Random Allocation; Reproducibility of Results; regeneration; reprodukovatelnost výsledků; spotřeba kyslíku; Oxygen Consumption; Time Factors; velikost těla; mužské pohlaví; Energy Metabolism; ještěři; Regeneration; hmotnostní přírůstek; regenerace; energetický metabolismus; Basal Metabolism; oxygen consumption; zvířata; growth; Tail; náhodné rozdělení; časové faktory; autotomy; ocas; lizard; metabolic rate; Male; Animals